Same Same But Different: Dialects and Trade - Alfred Lameli; Volker Nitsch; Jens Suedekum; Nikolaus Wolf (Center for Economic Studies and ifo Institute (CESifo), 2013)
Language is a strong and robust determinant of international trade patterns: Countries sharing a common language trade significantly more with each other than countries using different languages, holding other factors constant. In this paper, we show that this trade-promoting effect of language is likely to reflect cultural ties, rather than lower costs of communication or similar institutions. Analyzing unique data for a single-language country, Germany, we find that similarities in the local dialect between regions have a sizable and significant positive impact on intra-national trade. We interpret this finding as evidence for the effect of culture on trade.
Keywords: F14; F15; Z10; 330; language; culture; trade costs; gravity